Diploma Course on Digital Agriculture in Guatemala - Jiménez, Daniel; Martínez, Jesús David; Muñoz, Armando; García, Ramiro; Borrayo, Andrea; Ramírez Villegas, Julián Armando; Sandoval, Victor (2022)
CGIAR Research Initiatives on Digital Innovation and AgriLAC Resiliente have collaborated with different stakeholders to implement digital agriculture approaches for professionals in critical locations in the Central American Dry Corridor in 2022. The university diploma course aimed to strengthen the technical capacity of agricultural professionals in digital agriculture and allow them to make more informed, data-driven decisions in agrifood systems. The 90-hour diploma course is organized in to five modules (i) Human-centered design and digital inclusion, (ii) Data collection, data management, and data integration, (iii) Data science, (iv) Crop modeling, and (v) scaling digital innovations. Twenty-six agricultural professionals from various institutions, from government, non-government organizations (NGOs), growers' associations, and educational institutions to the private sector, completed the course on 16 December 2022.